Enhanced tolerance to salinity stress in grapevine plants through application of carbon quantum dots functionalized by proline - Gohari, Gholamreza; Panahirad, Sima; Sepehri, Nasrin; Akbari, Ali; Zahedi, Seyed Morteza; Jafari, Hessam; Dadpour, Mohammad Reza; Fotopoulos, Vasileios (My University, 2021)
Salinity has destructive impacts in plant production; therefore, application of new approaches such as nanotechnology and plant priming is attracting increasing attention as an innovative means to ameliorate salt stress effects. Considering the unique properties and recorded beneficial influence of carbon quantum dots (CQDs) and proline in plant growth and physiological parameters when applied individually, their conjugation in the form of carbon quantum dot nanoparticles functionalized by proline (Pro-CQDs NPs) could lead to synergistic effects. Accordingly, an experiment was conducted to evaluate the impact of this advanced nanomaterial (Pro-CQDs NPs) as a chemical priming agent, in grapevine plants cv. 'Rasha'. For this purpose, proline, CQDs, and Pro-CQDs NPs at three concentrations (0, 50, and 100 mg L-1) were applied exogenously 48 h prior to salinity stress (0 and 100 mM NaCl) that was imposed for a month. Three days after imposing salt stress, an array of biochemical measurements was recorded, while agronomic and some physiological parameters were noted at the end of the stress period. Results revealed that proline treatment at both concentrations, as well as CQDs and Pro-CQDs NPs at low concentration, positively affected grapevine plants under both non-stress and stress conditions. Specifically, the application of proline at 100 mg L-1 and Pro-CQDs NPs at 50 mg L-1 resulted in optimal performance identifying 50 mg L-1 Pro-CQDs NPs as the optimal treatment. Proline treatment at 100 mg L-1 increased leaf fresh weight (FW) and dry weight (DW); chl a, b, and proline content; SOD activity under both non-stress and stress conditions; Y (II) under salinity and carotenoid content; and CAT activity under control conditions. Pro-CQDs NP treatment at 50 mg L-1 enhanced total phenol, anthocyanin, and Fv/Fo, as well as APX and GP activities under both conditions, while increasing carotenoid, Y (II), Fv/Fo, and CAT activity under salinity. Furthermore, it decreased MDA and H2O2 contents at both conditions and EL and Y (NO) under salt stress. Overall, conjugation of CQDs with proline at 50 mg L-1 resulted in further improving the protective effect of proline application at 100 mg L-1. Therefore, functionalization of NPs with chemical priming agents appears to be an effective means of optimizing plant-priming approaches towards efficient amelioration of abiotic stress-related damage in plants.
Keywords: Abiotic stress; Antioxidants; Chemical priming; Grapevine; Nanoparticles